2022
DOI: 10.3389/fcimb.2021.814276
|View full text |Cite
|
Sign up to set email alerts
|

Cruzipain Sulfotopes-Specific Antibodies Generate Cardiac Tissue Abnormalities and Favor Trypanosoma cruzi Infection in the BALB/c Mice Model of Experimental Chagas Disease

Abstract: Trypanosoma cruzi cruzipain (Cz) bears a C-terminal domain (C-T) that contains sulfated epitopes “sulfotopes” (GlcNAc6S) on its unique N-glycosylation site. The effects of in vivo exposure to GlcNAc6S on heart tissue ultrastructure, immune responses, and along the outcome of infection by T. cruzi, were evaluated in a murine experimental model, BALB/c, using three independent strategies. First, mice were pre-exposed to C-T by immunization. C-T-immunized mice (C-TIM) showed IgG2a/IgG1 <1, induced the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 98 publications
(158 reference statements)
0
2
0
Order By: Relevance
“…The choice of sub-lethal dose was due to avoid mice mortality in order to analyze the immunopathogenesis is process that occurs in post-acute phase on target tissues pre-exposed to sulfotopes. The murine model was selected because of its susceptibility and auto-reactivity, and it has been previously demonstrated as an outstanding archetype since (a) its immune response profile to T. cruzi infection has long been established to be well-known; (b) the murine strain selected has the ability to imitate both phases, acute and chronic phase models ( Cardoni et al., 1999 ); (c) along the acute phase, it survives increased parasitemia ( Cardoni et al., 1999 ; Wrightsman et al., 1982 ); (d) this strain constitutes a chronic model, which allows one to cautiously examine tissue pathogenesis in the chronic phase ( Cardoni et al., 1999 ; Roggero et al., 2002 ; Soprano et al., 2022 ); and (e) simply, the selected female mice are more resistant to the progress of infection by T. cruzi . Despite the fact that, in T. cruzi infection, the strain does not present as marked polarization as it was observed in Leishmaniasis, BALB/c mice have a biased response towards Th2 ( Huang et al., 1997 ; Kuroda et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of sub-lethal dose was due to avoid mice mortality in order to analyze the immunopathogenesis is process that occurs in post-acute phase on target tissues pre-exposed to sulfotopes. The murine model was selected because of its susceptibility and auto-reactivity, and it has been previously demonstrated as an outstanding archetype since (a) its immune response profile to T. cruzi infection has long been established to be well-known; (b) the murine strain selected has the ability to imitate both phases, acute and chronic phase models ( Cardoni et al., 1999 ); (c) along the acute phase, it survives increased parasitemia ( Cardoni et al., 1999 ; Wrightsman et al., 1982 ); (d) this strain constitutes a chronic model, which allows one to cautiously examine tissue pathogenesis in the chronic phase ( Cardoni et al., 1999 ; Roggero et al., 2002 ; Soprano et al., 2022 ); and (e) simply, the selected female mice are more resistant to the progress of infection by T. cruzi . Despite the fact that, in T. cruzi infection, the strain does not present as marked polarization as it was observed in Leishmaniasis, BALB/c mice have a biased response towards Th2 ( Huang et al., 1997 ; Kuroda et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the left part of the figure, it can be observed that in the absence of infection, the sulfotopes’ pre-exposition that determines an immune response and the passive treatment with antibodies specific for sulfotopes determine immunopathogenesis with the consequent characteristics on ultrastructural alterations on cardiac muscle tissues. On the right part of the figure, it can be observed that the sulfotopes’ pre-exposition and the passive treatment with antibodies specific for sulfotopes, followed by challenge with trypomastigotes, favor parasite infection, thus increasing parasitemia ( Soprano et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%